1990
DOI: 10.1080/01652176.1990.9694242
|View full text |Cite
|
Sign up to set email alerts
|

Observations on avian intestinal spirochaetosis

Abstract: SUMMARY Three SPF-laying hens were inoculated into the crop with avian intestinal spirochaetes which previously had been passaged in broiler chicks by oral inoculation (isolate 1380). Mild persisting gastrointestinal disorder developed; at nine months post inoculation spirochaetes were readily demonstrated in caecal faeces. Histologic examination of the caecal mucosa revealed many spirochaetes covering the mucosal surface and filling up the crypts lumina. Spirochaetes were found in intra-and subepithelial loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…Spirochaetes inhabiting the intestinal tract of birds have been noted (Harris, 1930;Mathey et al, 1955;Davelaar et al, 1985Davelaar et al, , 1986Griffiths et al, 1987;Dwars et al, 1989Dwars et al, , 1990) whilst spirochaetes of porcine origin have been shown to colonize the caeca of young broiler chicks (Adachi et al, 1985;Sueyoshi et al, 1990). In experimental infections with avian intestinal spirochaetes in broilers kept in isolators a reduction in body weight, a reduction in the concentration of carotenoids in the serum, and an increase of the activity of alkaline phosphatase in the serum was found (Davelaar et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Spirochaetes inhabiting the intestinal tract of birds have been noted (Harris, 1930;Mathey et al, 1955;Davelaar et al, 1985Davelaar et al, , 1986Griffiths et al, 1987;Dwars et al, 1989Dwars et al, , 1990) whilst spirochaetes of porcine origin have been shown to colonize the caeca of young broiler chicks (Adachi et al, 1985;Sueyoshi et al, 1990). In experimental infections with avian intestinal spirochaetes in broilers kept in isolators a reduction in body weight, a reduction in the concentration of carotenoids in the serum, and an increase of the activity of alkaline phosphatase in the serum was found (Davelaar et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the role of intestinal spirochaetes as pathogens of chickens has increased in recent years, following the publication of a series of reports implicating these bacteria as a cause of diarrhoea, reduced egg produc tion and/or faecal staining of eggshells in layer and broiler breeder ocks in the Netherlands (Davelaar et al, 1986;Dwars et al, 1989Dwars et al, , 1990Dwars et al, , 1992bDwars et al, , 1993Sm it et al, 1998) , England (Grif® ths et al, 1987) , the USA (Swayne et al, 1992;Tram pel et al, 1994), and Australia (McLaren et al, 1996) . The bacteria involved were all weakly haem olytic, but otherwise were poorly characterized, and it was not clear whether the various reports even referred to spirochaetes of the sam e species.…”
Section: Introductionmentioning
confidence: 99%
“…Colonization tends to be chronic in adult birds in infected flocks (Dwars et al, 1990), and has been associated with a variety of symptoms including diarrhoea, increased faecal fat content, faecal staining of eggshells, delayed onset of egg laying, reduced egg weights, reduced growth rates, increased feed consumption and poor digestion of feed (Davelaar et al, 1986;Griffiths et al, 1987;Dwars et al, 1990;Swayne et al, 1992;Dwars et al, 1992aDwars et al, , 1993Trampel et al, 1994). Broiler flocks derived from the offspring of breeder flocks infected with spirochaetes have been shown to have poorer feed conversion, an increased number of weak chicks, slower growth and a poorer feed digestion than the offspring of flocks where spirochaetes are not present (Smit et al, 1998).…”
Section: Introductionmentioning
confidence: 99%